1959
DOI: 10.1002/macp.1959.020320114
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular branching in polyvinyl acetate

Abstract: The polymerisation of vinyl acetate at various temperatures between+l8 "C. and -50°C. to various conversions has been carried out to obtain polymers with different degrees of branching. All polymer samples showed a fall in intrinsic viscosity after hydrolysis and reacetylation. This change is related to the amount of branching in the original polymer. but the relationship did not become clear for unfractionated material. One sample was fractionated, and the fractions studied by following the changes in intrins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

1960
1960
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 19 publications
3
15
0
Order By: Relevance
“…After C2 injection at t=15 min, a clear decrease of temperature followed by the increase and stagnation of pressure ( Figure 5) implied that the growing VDF-radicals were consumed by C2 units and no further propagation occurred. This is further confirmed by alike 1 H ( Figure 6) and 19 F (Figure 7) NMR spectra chemical shifts.…”
Section: Influence Of Ethylene Pressure and Initiator Concentrationsupporting
confidence: 67%
See 2 more Smart Citations
“…After C2 injection at t=15 min, a clear decrease of temperature followed by the increase and stagnation of pressure ( Figure 5) implied that the growing VDF-radicals were consumed by C2 units and no further propagation occurred. This is further confirmed by alike 1 H ( Figure 6) and 19 F (Figure 7) NMR spectra chemical shifts.…”
Section: Influence Of Ethylene Pressure and Initiator Concentrationsupporting
confidence: 67%
“…The 1 H NMR spectra obtained were calibrated with the aid of d6-DMSO peak (2.5 ppm). 19 F NMR were calibrated utilising a CF 3 peak from the fluorinated surfactant. 19 F NMR was used to determine the types of VDF additions in the polymer chain (i.e.…”
Section: Injection Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Long chain branching is not easily quantified by NMR spectroscopy alone as the branch points are liable to be confused with those of the short branches produced by backbiting. It has also been shown that significant backbiting occurs in the polymerization of VAc [75][76][77] . Bugada et al 69 employed 13 C and 1 H NMR to determine total, i.e.…”
Section: Mechanism Of Transfer To Poly(vinyl Acetate)mentioning
confidence: 99%
“…One well‐known route to aldehyde‐terminated water‐soluble polymers is the selective oxidation of the minor fraction of cis ‐diol units within poly(vinyl alcohol) [42] . This water‐soluble polymer can be obtained via hydrolysis of poly(vinyl acetate), which contains such cis ‐diols as defect sites resulting from a small amount of head‐to‐head coupling during the free radical homopolymerization of vinyl acetate [43] . Oxidation is readily achieved in aqueous solution under mild conditions using sodium periodate to afford aldehyde‐capped poly(vinyl alcohol) chains [44] .…”
Section: Introductionmentioning
confidence: 99%